China’s presence in the South American region. Its implications in the field of security - Novak, Fabián (2022)
In this regard, this policy paper focuses on analyzing and comparing the contents of the six aforementioned studies comprising the book, from which the following general conclusions were reached: The insertion of the People’s Republic of China in Latin America, particularly in the six countries participating in the Security Policy Network, has been characterized by the subtlety of its approach, i.e., by the use of soft power mechanisms, thus far not seeking visibility, a dramatic alteration of the pre-existing conditions or a confrontation with the United States in what is considered the immediate sphere of U.S. influence. China’s penetration in South American countries is characterized by pragmatism (not conditioned to ideologies, values or principles), flexibility (it adapts to each country’s circumstances or characteristics) and differentiation (depending on the country in question), essentially concentrating on the economic field. China’s insertion in South American countries was initially through trade, investment and financing. This was encouraged by the increase in raw materials prices in the countries and by China’s accelerated import of these raw materials (food, minerals, etc.), which generated significant profits and benefits for both parties. It also, however, meant these countries’ greater dependence on the Asian superpower, as well as the intensification of their primary export structure. The 2008 crisis accelerated China’s capital exports, which translated into strong direct investments in South American States, increasing even more their dependence on the Asian giant. Subsequently, China has sought a more comprehensive relationship with the region’s countries through its 2008 and 2016 plans for Latin America and the Caribbean, in some cases succeeding in forming strategic partnerships. Doing so ensures a relationship not limited to the economic sphere but extended to the political, social, military and cultural ones, thus increasing China’s support and influence in the world. The U.S. perceives this insertion as a threat, although it seems not to have a strategy for regional containment of China, let alone a policy against the region’s States that are moving closer to it. In contrast, most South American countries seem not to perceive a threat from China’s insertion, at least if it remains essentially concentrated in the economic field, as it has been up to now. Moreover, unlike China’s vision, most South American countries perceive the Asian power only or mainly as an economic partner and not as a political ally. With the exception of Bolivia, the other five countries studied are taking advantage of their relationship with China to increase their trade income, attract investments and obtain loans from that country, all favorable to their economic and social development. At the same time, they are seeking to keep the U.S. as their strategic ally, maintaining the values and principles it postulates. It is why these countries are trying to avoid aligning with China or approving measures either superpower could perceive as aggressive.